2013
DOI: 10.1136/bjophthalmol-2013-303189
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes after epiretinal membrane peeling combined with cataract surgery

Abstract: Combined surgery for ERMs and cataracts may potentially be as effective as membrane peeling alone with respect to visual and anatomical outcomes. Further studies are necessary to determine if there may be greater ERM recurrence or need for reoperation after combined surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…Regarding the safety profile of the combined surgery, the complication rates were relatively low and similar to those reported in previous studies [10][11][12][13] . Unlike our findings, several authors reported a high rate of anterior chamber fibrinous reaction, posterior synechiae and persistent macular edema in combined pars plana vitrectomy and cataract surgery when compared to consecutive procedures [30][31][32] .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Regarding the safety profile of the combined surgery, the complication rates were relatively low and similar to those reported in previous studies [10][11][12][13] . Unlike our findings, several authors reported a high rate of anterior chamber fibrinous reaction, posterior synechiae and persistent macular edema in combined pars plana vitrectomy and cataract surgery when compared to consecutive procedures [30][31][32] .…”
Section: Discussionsupporting
confidence: 72%
“…Cataract is a common side effect that may take place within 2 years after the procedure, and its combined surgical management seems to allow functional outcomes equivalent to consecutive surgeries [10][11][12][13] .…”
mentioning
confidence: 99%
“…However, difficulties with capsulorhexis, higher postoperative inflammation, intraoperative miosis, and corneal edema with Descemet's folds are disadvantages when combining cataract and vitreoretinal surgery [8, 9]. Moreover, in combined surgeries for epiretinal membrane, increased postoperative macular thickness and recurrence of epiretinal membrane have been reported [10]. …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Since cataract arises in most phakic patients within 2 years after ERM removal, it has been demonstrated that the combination of these 2 procedures allows equivalent outcomes to consecutive surgery with lower costs and fewer constraints. [20][21][22][23] Nevertheless, in some cases and despite successful peeling without complications, functional outcome may be disappointing. It is therefore necessary to identify preoperative prognostic factors for good postoperative visual recovery.…”
mentioning
confidence: 95%